Geranium janakianum (Geraniaceae), a new species from Uttarakhand, India - Shukla, Aparna R.; Sahu, Nayan; Hurrah, Imtiyaz A.; Ahmad, Mairaj; Wagh, Vijay V. (Phytotaxa, 2023)
A new species, Geranium janakianum, is described and illustrated here from Uttarakhand State, India. Photographs and a comparison of the diagnostic features of the new taxon with those of the morphologically similar species, G. himalayense and G. wlassovianum, are provided. These three species are characterised by palmatipartite leaves and relatively less lobed leaf segments. However, G. janakianum is clearly distinguished from its close relatives by having a pentamerous leaf lamina, rounded petal apex, micro-morphological features of the seed, mericarp and pollen in addition to the presence of stomata all over the plant.